Pengaruh Lingkungan Keluarga yang Religius terhadap Motivasi Belajar Siswa - Suriani, Irda (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2022)
The background to this research problem is a religious family environment on the learning motivation of class V students at SD Muhammadiyah 2 Padangsidimpuan. A religious family environment will provide peace in the home, so that students' learning motivation will increase compared to students who have a less religious family environment. The formulation of the problem in this research is whether there is an influence of a religious family environment on the learning motivation of class V students at SD Muahamadiyah 2 Padangsidimpuan. The purpose of this research is to determine whether or not a religious family environment influences the learning motivation of class V students at SD Muahammadiyah 2 Padangsidimpuan. This research method is quantitative research with an ex post facto approach. The research results show that the religious family environment of class V students at SD Muahamadiyah 2 Padangsidimpuan can be said to be good with a score of 81%, while the learning motivation of class V students can be said to be good with a score of 71.53%. The results of this research explain that there is a significant influence between a religious family environment and student learning motivation, which was found by the t test that tcount is 5.045 ttable is 1.674 with n=50 and significance is 0.05, so H0 is rejected and Ha is accepted so it can be It was concluded that there was a significant influence between a religious family environment and student learning motivation.